2010
DOI: 10.1089/omi.2009.0100
|View full text |Cite
|
Sign up to set email alerts
|

A Persistent and Diverse Airway Microbiota Present during Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are a major source of morbidity and contribute significantly to healthcare costs. Although bacterial infections are implicated in nearly 50% of exacerbations, only a handful of pathogens have been consistently identified in COPD airways, primarily by culturebased methods, and the bacterial microbiota in acute exacerbations remains largely uncharacterized. The aim of this study was to comprehensively profile airway bacterial communities using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
5
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(216 citation statements)
references
References 42 publications
13
195
5
3
Order By: Relevance
“…Huang and coworkers (22) provide a possible explanation from their study on the changes in diversity of microorganisms in the lung microbiome associated with length of intubation in patients with acute exacerbations of COPD. They found that individuals with higher bacterial community diversity also supported a higher number of Firmicutes and those with less bacterial diversity had a higher number of Proteobacteria (22). This is consistent with our findings, and in those with severe COPD (21), that a low bacterial diversity could lead to an increase in the Proteobacteria phylum and a higher bacterial diversity could lead to an increase in the Firmicutes phylum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Huang and coworkers (22) provide a possible explanation from their study on the changes in diversity of microorganisms in the lung microbiome associated with length of intubation in patients with acute exacerbations of COPD. They found that individuals with higher bacterial community diversity also supported a higher number of Firmicutes and those with less bacterial diversity had a higher number of Proteobacteria (22). This is consistent with our findings, and in those with severe COPD (21), that a low bacterial diversity could lead to an increase in the Proteobacteria phylum and a higher bacterial diversity could lead to an increase in the Firmicutes phylum.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in frequency and severity of exacerbations that occurs with the progression of COPD might be a manifestation of this vicious cycle of infection and inflammation (19). The recent report of Hilty and coworkers (20) of bronchial brush samples showing that a microbiome exists in the normal smoker's lung and that this microbiome changes in COPD has stimulated additional studies of the lung microbiome based on either bronchial brushings, bronchoalveolar lavage (BAL) specimens, endotracheal aspirates, or lung tissue (21,22). This current study uses lung tissue samples and extends these previous findings by providing an in-depth analysis of the bacterial microbiome in lung tissue from patients with very severe COPD (GOLD 4), nonsmoking and smoking control subjects, and individuals with cystic fibrosis (CF).…”
mentioning
confidence: 99%
“…Recently, molecular cultureindependent techniques have identified complex microbial communities in the lower airways with distinct alterations in the microbiome occurring in a number of respiratory conditions [42][43][44]. Molecular techniques enable a full visualisation of the microbiota in any given environment.…”
Section: The Role Of Bacteria In the Pathogenesis Of Ipfmentioning
confidence: 99%
“…31 In recent studies of COPD, in addition to identified by culture, the persistence of other potentially pathogenic bacteria was showed only by molecular methods and has been associated with severe attacks. 32 In studies with the PCR method, isolation of the bacterial agent and mixed infectious agents demonstrated a significant increase in the culture. Compared to serological methods, the frequency of atypical agents was found to be less and the use of antibiotics for atypical pathogens with no change in clinical results was observed.…”
Section: Etıology Of Exacerbatıonsmentioning
confidence: 99%